Study on self-esteem and academic stress of university students. - Joshi, Yadav Prasad (2007)
ABSTRACT: A Study on Self-Esteem and Academic Stress of University Students was carried out among the 2nd year students of Faculty of Humanities and Social Sciences, Tribhuvan University, Central Campus Kirtipur in between May 2005 to July 2006. A total of 150 students ( Males=75, Female 75) were purposively selected and subjected to fill up structured questionnaires of Rosenberg Self-esteem Scale (SES) and Scale for Assessing Academic Stress (SAAS). The study found that mean value of self-esteem score among males was 19.160 which was greater than those females (17.653) and standard deviation of self-esteem scores among males and females was 3.141 and 3.387 respectively. The mean values of self-esteem score among males and females with the ratio 2.838 at 74 d. f. was significant at. 0.1 level. The analysis of variance of self-esteem scores among males and females with the F ratio 7.979 at 149 d. f. which was statistically significant at . 01 level. The mean stress score obtained by the females was slightly greater (Males= 13.880 and Females=13.907) than that of males and standard deviation of stress scores among boys and girls were found to be 4.577 and 4.316 respectively. Comparing the mean value of stress score among males and females with t-statistic (t-ratio=-0.038) at 74 d. f. which was found to be not significant at .01 level. It indicates that females achieved more scores in stress than males. The F ration of stress scores among males and females was found to be 0.971, at 149 d. f. which was significant at .01 level. Correlation between self-esteem and stress among girls was found to be negative (-0.241) which is statistically significant at 0.05 level of significance as well as negative correlation was also found in stress score and self-esteem score among boys (-0.412) which is statistically significant at 0.01 level of significance. Since low self-esteem and high academic stress were found among females in comparison of males. Therefore, as a consequence, university departments or professionals should take into consideration about this effect and they could develop programs for university students in order to enhance self-esteem and deal with academic stress.